Methylotrophic methanogenesis and potential methylated substrates in marine sediment - Zhuang, Guangchao (Universität Bremen, 2014)
Methane is the simplest hydrocarbon and a potent greenhouse gas that plays important roles in atmospheric chemistry, the global carbon cycle, and the formation of gas hydrates in marine sediment. Microbial production of methane is the terminal step during the degradation of organic matter. It is generally thought that methane is predominantly produced from hydrogenotrophic and acetoclastic methanogenesis, while methylotrophic methanogenesis and its relative importance for methane production in marine sediments remain largely unconstrained. The main objective of this study is to constrain potential methylated substrates and methylotrophic methanogenic activities, and further evaluate the importance of methylotrophic methanogenesis in marine sediment. As the lack of knowledge on in situ concentrations of methylated compounds impedes our understanding on their quantitative contribution to methane production, the first step was to determine the concentrations and carbon isotopic composition of methylated compounds using newly-developed methods. Quantitative or isotopic analysis of methanol, trimethylamine (TMA) and dimethylsulfide (DMS) in marine sediment and pore waters were achieved using gas chromatographic approaches in combination with a range of pretreatment techniques. Using these protocols, the concentrations and distributions of methylated compounds were determined in a variety of marine sediments from Aarhus Bay in Denmark, Orca Basin in the Gulf of Mexico and Gulf of Lions in the northwestern Mediterranean Sea. To further constrain the importance of methylotrophic methanogenesis, two case studies combining the newly-developed methods as well as various biogeochemical analyses were performed in hypersaline sediment and estuarine sediment. In hypersaline sediment of Orca Basin, multiple lines of evidences from abundances of methanogenic substrates, carbon isotope systematics between methane and substrates, thermodynamic calculations, stable isotope tracer and radiotracer experiments as well as gene and ...